2020
DOI: 10.3390/su12135441
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Transformations in Ukraine towards the Sustainable Development of Agriculture

Abstract: The social and economic conditions of all market participants are incentives and constraining factors influencing the levels of food, social, economic and ecologic security. The purpose of the article lies in the presentation of the author’s concept of the social and economic conditions where the transformation of economic relations between agrofood market participants is happening—in particular, the livestock products market of Ukraine—and the assessment of the state of food security of the country, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Won Kie [18] concluded that there is a negative relationship between fund performance and liquidity and a non-linear relationship between them. Nie et al [19] analyzed the dynamics in the investment costs, O. Kravchenko et al [20] and R. Khirivskyi et al [21] pointed out that an effective model of the agri-food and land markets should provide for a systematic development in a stable vector that takes into account the synergistic effect and the internal potential of the economic system. B. Fetai [22] determined that the impact of financial integration depends on the development of internal financial markets, macroeconomic stability and the quality of institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Won Kie [18] concluded that there is a negative relationship between fund performance and liquidity and a non-linear relationship between them. Nie et al [19] analyzed the dynamics in the investment costs, O. Kravchenko et al [20] and R. Khirivskyi et al [21] pointed out that an effective model of the agri-food and land markets should provide for a systematic development in a stable vector that takes into account the synergistic effect and the internal potential of the economic system. B. Fetai [22] determined that the impact of financial integration depends on the development of internal financial markets, macroeconomic stability and the quality of institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous scientific publications are also focused on other important aspects of the problem of rural population employment, social and economic transformations in the agrarian sector, identification of the problems and prospects of sustainable development of rural territories, particularly in the context of decentralization, European integration and globalization [36][37][38][39][40][41][42][43][44][45][46][47][48][49]. However, in spite of the great scope of scientific research, the issues of determination of the factors influencing employment in the domestic agriculture, need a deeper investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Urban agriculture is a topical subject of scientific research today. In previous publications, the authors dealt with state intervention on agricultural land [ 5 ], comparing Poland and Ukraine in terms of agricultural development and production scale [ 6 , 7 ]. Recent studies also concerned access to green areas in cities and the way these areas are used [ 8 ].…”
Section: Introductionmentioning
confidence: 99%